Sports coaching in an online space: What can we learn from endurance sport coaches? - Blanchfield, J.; McArdle, J.; Haughey, T. (International Sport Coaching Journal, 2023)
Within endurance sports (ES), a practice exists in which online remote coaching (RC) is a necessary construct. This study aimed to examine the processes of ES coaches to gain insight into the experiences of coaches engaging in RC before COVID-19 forced others to do the same. To achieve this aim, semistructured interviews were conducted with ES coaches (N = 7; M = 6, F = 1). Transcripts were subject to thematic analysis, with three dimensions (a) remote coach and ES, (b) process of remote coaching, and (c) delivery of training online being identified. An additional 17 higher and 79 lower order themes were found. Results found that to be effective online, ES coaches utilised technology such as instant messaging and online software to increase presence and decrease the perceived distance from athletes. They aimed to create autonomous athletes both by choice and by necessity. The ease of access through technology had a negative and positive impact on work-life balance. A process was developed whereby only technology that served a purpose to further athlete outcomes was used and balanced with subjective feedback. Further research is needed to garner athlete expectations and experiences of RC.